Vytápění a větrání výrobní a skladové haly - Bližňák, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Cílem této diplomové práce je navrhnout systém vytápění a větrání průmyslové a skladové haly a přilehlé administrativní části objektu. Základem návrhu je výpočet tepelných ztrát a tepelných zisků objektu. Návrh systémů má za cíl dosáhnout požadovaného mikroklimatu pro jednotlivé prostory a provozy. Systém vytápění, větrání a chlazení je zpracován v přiložené výkresové dokumentaci.

The objective of this master thesis is to design heating and ventilation systems for a production and storage hall and a contiguous administrative part of the building. The basis of design is in calculation of thermal losses and gains of the building. The objective of design is to reach requisite microclimate for single spaces and operations. System of heating, ventilation and cooling are elaborated in drawing documentation.
Ventilation and heating system of a production and storage hall
Keywords: Vytápění; větrání; chlazení; tepelné ztráty; tepelné zisky.; Heating; ventilation; cooling; heat losses; heat gains.